Cardiovascular phenotype of nonalcoholic fatty liver disease: Hanging the paradigm about the role of distant toxic fat accumulation on vascular disease - Sookoian, Silvia Cristina (2012)
We read with great interest the article by Kim et al. about the association between nonalcoholic fatty liver disease (NAFLD) and coronary artery calcification (CAC). The authors concluded that NAFLD per se might be a risk factor for coronary artery disease (CAD) as the association was “above and beyond visceral adiposity (VAT).”1 Interestingly, the Framingham Heart Study showed that VAT, body mass index, and pericardial fat (PCF) are associated with CAC, but only PCF remains significant following risk factor adjustment, suggesting a locally toxic effect of PCF on the vasculature.2 Thus, Kim et al. still leave open a key question about whether the contribution of NAFLD to CAC is above and beyond PCF. That would be an interesting hypothesis to test, even though the current evidence linking NAFLD, carotid artery wall thickness, and plaque development strongly suggests so.3